Clinical Characterization of Patients With Autosomal Dominant Short Stature due to Aggrecan Mutations - Gkourogianni, Alexandra; Andrew, Melissa; Tyzinski, Leah; Crocker, Melissa; Douglas, Jessica; Dunbar, Nancy; Fairchild, Jan; Funari, Mariana F A; Heath, Karen E; Jorge, Alexander A L; Kurtzman, Tracey; LaFranchi, Stephen; et al. (The Journal of clinical endocrinology and metabolism, 2017)
Context: Heterozygous mutations in the aggrecan gene (ACAN) cause autosomal dominant short stature with accelerated skeletal maturation. Objective: We sought to characterize the phenotypic spectrum and response to growth-promoting therapies. Patients and Methods: One hundred three individuals (57 females, 46 males) from 20 families with autosomal dominant short stature and heterozygous ACAN mutations were identified and confirmed using whole-exome sequencing, targeted next-generation sequencing, and/or Sanger sequencing. Clinical information was collected from the medical records. Results: Identified ACAN variants showed perfect cosegregation with phenotype. Adult individuals had mildly disproportionate short stature [median height, -2.8 standard deviation score (SDS); range, -5.9 to -0.9] and a history of early growth cessation. The condition was frequently associated with early-onset osteoarthritis (12 families) and intervertebral disc disease (9 families). No apparent genotype-phenotype correlation was found between the type of ACAN mutation and the presence of joint complaints. Childhood height was less affected (median height, -2.0 SDS; range, -4.2 to -0.6). Most children with ACAN mutations had advanced bone age (bone age - chronologic age; median, +1.3 years; range, +0.0 to +3.7 years). Nineteen individuals had received growth hormone therapy with some evidence of increased growth velocity. Conclusions: Heterozygous ACAN mutations result in a phenotypic spectrum ranging from mild and proportionate short stature to a mild skeletal dysplasia with disproportionate short stature and brachydactyly. Many affected individuals developed early-onset osteoarthritis and degenerative disc disease, suggesting dysfunction of the articular cartilage and intervertebral disc cartilage. Additional studies are needed to determine the optimal treatment strategy for these patients.
Keywords: mutace; dospělí; heterozygot; Aggrecans; agrekany; Female; Infant; Anthropometry; Phenotype; růst; dítě; předškolní dítě; Pedigree; Adult; Growth Hormone; ženské pohlaví; mutační analýza DNA; mladý dospělý; Brachydactyly; rodokmen; Adolescent; Osteochondritis Dissecans; lidé; Heterozygote; Intervertebral Disc Displacement; degenerace meziobratlové ploténky; osteochondritis dissecans; DNA Mutational Analysis; brachydaktylie; antropometrie; Aged, 80 and over; Mutation; Middle Aged; Intervertebral Disc Degeneration; výhřez meziobratlové ploténky; Male; kojenec; Aged; Child, Preschool; Young Adult; Growth; nanismus; Dwarfism; lidé středního věku; Child; senioři nad 80 let; senioři; mužské pohlaví; fenotyp; růstový hormon; mladiství; Humans